IMPLEMENTASI PEMBELAJARAN BERBASIS PROYEK MATA PELAJARAN PKN UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS IV SDN MERJOSARI 3 - Seran, Natalia Francelia; Kardiana Metha Rozhana; Chusnul Chotimah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Based on the results of observations in the fourth grade at SDN Merjosari 3 Malang, it was found that students’ critical thinking skills in Civic Education learning still need to be improved. This is indicated by the fact that some students are not yet able to analyze problems effectively, are not accustomed to expressing opinions logically, and are less active in providing arguments or responses to a given issue. In addition, students tend to be passive during discussions and have not been able to optimally relate the learning material to their daily lives.This study employed Classroom Action Research (CAR) conducted in two cycles. Each cycle consisted of planning, implementation, observation, and reflection stages. The subjects of the study were fourth-grade students of SDN Merjosari 3 Malang. Data collection techniques included observation sheets, learning outcome tests, and documentation. The data were analyzed using both qualitative and quantitative descriptive methods.The results of the study showed that the implementation of project-based learning in Civic Education could improve students’ critical thinking skills. In the initial condition, the class average score was 70 with a mastery percentage of 40%. After the implementation of Cycle I, the average score increased to 73.33 with a mastery percentage of 66.66%. In Cycle II, the average score further increased to 89.00 with a mastery percentage of 86.66%.In conclusion, the implementation of project-based learning is effective in improving students’ critical thinking skills in Civic Education for fourth-grade students at SDN Merjosari 3 Malang. This approach encourages students to be more active in the learning process through activities that involve problem-solving, analysis, and decision-making. Therefore, learning becomes more meaningful as students are directly engaged in the learning experience, which positively impacts the development of their critical thinking skills.